2020
DOI: 10.1007/s11103-020-01091-y
|View full text |Cite
|
Sign up to set email alerts
|

GmNAC06, a NAC domain transcription factor enhances salt stress tolerance in soybean

Abstract: Key message We found GmNAC06 plays an important role in salt stress responses through the phenotypic, physiological and molecular analyses of OE, VC, and Mutant composite soybean. Abstract Salinization affects 20% of all cultivated land worldwide because of the high salinity of irrigation water and the excessive use of water, and this amount is increasing daily. NAC (NAM, ATAF, and CUC) have been found to be involved in salt stress. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 69 publications
4
89
0
Order By: Relevance
“…A large number of NAC-encoding genes have been identified and confirmed in various plants for their role in regulating wood formation [14], leaf senescence [15], fruit development [16,17], and flower morphogenesis [18,19]. Furthermore, NAC TFs also are involved in various biotic and abiotic stress responses in many plants such as Populus tomentosa [20], Arabidopsis thaliana [21], Oryza sativa [22,23], Glycine max [24], Arachis hypogaea [25], and Xanthoceras sorbifolia [26]. The overexpression of many NAC genes increases stress tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of NAC-encoding genes have been identified and confirmed in various plants for their role in regulating wood formation [14], leaf senescence [15], fruit development [16,17], and flower morphogenesis [18,19]. Furthermore, NAC TFs also are involved in various biotic and abiotic stress responses in many plants such as Populus tomentosa [20], Arabidopsis thaliana [21], Oryza sativa [22,23], Glycine max [24], Arachis hypogaea [25], and Xanthoceras sorbifolia [26]. The overexpression of many NAC genes increases stress tolerance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated a direct function of the OsNAC041 gene under salt stress and can offer an excellent potential to target other NAC genes for rice-resistant breeding (Bo et al, 2019 ). Similarly, another NAC gene GmNAC06 was targeted by using CRISPR/Cas9-based gene editing and overexpression technology in soybean, and the results demonstrated that the GmNAC06 gene improved the salinity tolerance by alleviating ROS effects, accumulating glycine betaine and proline, and maintaining ionic homeostasis (Li et al, 2021 ).…”
Section: The Era Of Plant Genome Editingmentioning
confidence: 99%
“…After overexpression of OoNAC72 in Arabidopsis thaliana, Guan et al found that transgenic plants carry out osmotic regulation and remove ROS after salt stress so as to reduce peroxidation damage [31]. Li et al used gene editing combined with genetic transformation and other molecular biology techniques and found that GmNAC06 could reduce the content of ROS in plants through the accumulation of osmotic mediating substances, thereby increasing the salt tolerance of plants [32].…”
Section: Introductionmentioning
confidence: 99%